2012
DOI: 10.1007/s15010-012-0317-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of surgical site infections after open and laparoscopic colon and rectal surgeries on postoperative resource consumption

Abstract: This study quantified the impact of SSIs on resource consumption and confirmed significant cost variations among hospitals. These variations could not be explained by patient characteristics or infection type.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
34
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 18 publications
0
34
0
Order By: Relevance
“…A study from a single hospital in the UK found that the additional costs for patients who developed a SSI were £5239 (€5846) higher. Another study compared the costs of patients with, and without SSI between eight different hospitals in Japan and found the additional costs ranged from US $853 to US $5348 (€785–4925), with great variation between hospitals.…”
Section: Introductionmentioning
confidence: 99%
“…A study from a single hospital in the UK found that the additional costs for patients who developed a SSI were £5239 (€5846) higher. Another study compared the costs of patients with, and without SSI between eight different hospitals in Japan and found the additional costs ranged from US $853 to US $5348 (€785–4925), with great variation between hospitals.…”
Section: Introductionmentioning
confidence: 99%
“…Once it occurred, patients would suffering from pain, cost of treatments [3, 4], prolonged length of hospital stay, and intangible loss [5]. …”
Section: Introductionmentioning
confidence: 99%
“…Prevention of surgical site infections is an important step to reduce rates of morbidity and mortality and costs. [14][15][16] Several systematic reviews have shown that ERAS and SSIB pathways can decrease length of stay and rates of perioperative morbidity and surgical site infection. [3][4][5]7,10 To our knowledge, only 1 study has presented the combined effects of both evidence-based pathways in a single institution, 3 and only 2 studies evaluating standardized care pathways have been conducted in smaller community centres.…”
mentioning
confidence: 99%